The Plasmodium falciparum Artemisinin Susceptibility-Associated AP-2 Adaptin μ Subunit is Clathrin Independent and Essential for Schizont Maturation - Henrici, Ryan C; Edwards, Rachel L; Zoltner, Martin; van Schalkwyk, Donelly A; Hart, Melissa N; Mohring, Franziska; Moon, Robert W; Nofal, Stephanie D; Patel, Avnish; Flueck, Christian; Baker, David A; Odom John, Audrey R; et al. (mBio, 2020)
The efficacy of current antimalarial drugs is threatened by reduced susceptibility of Plasmodium falciparum to artemisinin, associated with mutations in pfkelch13 Another gene with variants known to modulate the response to artemisinin encodes the μ subunit of the AP-2 adaptin trafficking complex. To elucidate the cellular role of AP-2μ in P. falciparum, we performed a conditional gene knockout, which severely disrupted schizont organization and maturation, leading to mislocalization of key merozoite proteins. AP-2μ is thus essential for blood-stage replication. We generated transgenic P. falciparum parasites expressing hemagglutinin-tagged AP-2μ and examined cellular localization by fluorescence and electron microscopy. Together with mass spectrometry analysis of coimmunoprecipitating proteins, these studies identified AP-2μ-interacting partners, including other AP-2 subunits, the K10 kelch-domain protein, and PfEHD, an effector of endocytosis and lipid mobilization, but no evidence was found of interaction with clathrin, the expected coat protein for AP-2 vesicles. In reverse immunoprecipitation experiments with a clathrin nanobody, other heterotetrameric AP-complexes were shown to interact with clathrin, but AP-2 complex subunits were absent.IMPORTANCE We examine in detail the AP-2 adaptin complex from the malaria parasite Plasmodium falciparum In most studied organisms, AP-2 is involved in bringing material into the cell from outside, a process called endocytosis. Previous work shows that changes to the μ subunit of AP-2 can contribute to drug resistance. Our experiments show that AP-2 is essential for parasite development in blood but does not have any role in clathrin-mediated endocytosis. This suggests that a specialized function for AP-2 has developed in malaria parasites, and this may be important for understanding its impact on drug resistance.
Keywords: adaptorový proteinový komplex 2; malaria; Adaptor Protein Complex 2; Plasmodium falciparum; Organisms, Genetically Modified; Drug Resistance; protozoální proteiny; artemisininy; Clathrin; Schizonts; léková rezistence; Protozoan Proteins; Artemisinins; Protein Transport; genový knockout; geneticky modifikované organismy; membránové proteiny; adaptin trafficking complex; klathrin; endocytóza; transport proteinů; adaptor proteins; antimalarika; Endocytosis; Membrane Proteins; artemisinin susceptibility; schizonti; Gene Knockout Techniques; endocytosis; Antimalarials